Diskursus Pembangunan Poros Maritim Dunia: Telaah Kritis Kebijakan - Ema Ema; Amiruddin Saleh; Heri Budianto (Jurnal Komunikasi Pembangunan, 2018)
This study aimed to reveal the development discourses about the vision of Jokowi-JK World Maritime Axis. Discourse is a public communication in which power generates knowledge through discourses, systems thinking and ideas that then establish the concept that binds a country to the planned changes. Through the discussion of Regulation No. 16 of the year 2017 on maritime policy in Indonesia, it is linked to the context of the social, cultural, economic and political aspects that influenced it. By analysing critical discourses about disclosure and disinformation over injustice and supremacy in the discussion. Research carried out by government agencies regulation-makers, observers and the public. Research using a basic data source, a Regulation 16/2017 document, an interview with an author, observers and the public. Results of the analysis show that the micro level, Corpus text regulation, represents the vision of the power of the ' Neoliberal ' ideology and of open foreign political systems. Communicate relationships using the data, symbols, promise and purpose of the power. In the communication entity, a symbol of power used to give emphasis, doctrine, appeal, orders, and supporting policies. As for the level of meso, discursive events in the production process, there is institutional interest as the existence of the new ministership. To help realize the axis of vision of the World Maritime Jokowi-JK with distribution to foreign countries and international fora, hence the introduction of government capital investment projects. At the macro level, in the maritime limits that conflict with the Circumpolar Sea Indonesia poses a threat to the security and safety of our becomes territorial integrity. Institutionally the role of the maritime Coordinator's dominance to prevent the other wing of the Maritime Administration. While socially poor marine infrastructure leads to disparity between the West and East of Indonesia.